2005
DOI: 10.1002/tox.20104
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal production and molecular characterization of microcystins in Oneida Lake, New York, USA

Abstract: Oneida Lake, northeast of Syracuse, New York, in the United States, is a shallow eutrophic lake with a well-established toxic cyanobacterial population. Samples for DNA, toxin, and phycological analyses were collected from six stations throughout the summers of 2002 (78 samples) and 2003 (95 samples). DNA was amplified by PCR using primer sets specific to the nonribosomal microcystin synthetase complex (mcyB and mcyD). PCR analysis in 2002 indicated that the microcystin genes were present in the water column f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…For DNA analysis, a 1-cm diameter subsample was taken from the original filter using a cork borer. DNA was extracted using a modified phenol:chloroform:isoamyl alcohol (25:24:1) protocol as described in Hotto et al (2005). DNA was amplified by PCR using 4 different primer sets, separated by 1.5% agarose gel electrophoresis and visualized using ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For DNA analysis, a 1-cm diameter subsample was taken from the original filter using a cork borer. DNA was extracted using a modified phenol:chloroform:isoamyl alcohol (25:24:1) protocol as described in Hotto et al (2005). DNA was amplified by PCR using 4 different primer sets, separated by 1.5% agarose gel electrophoresis and visualized using ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%
“…Primer sequences and conditions used for PCR were specific to the cyanobacterial 16S rRNA (CYA), Microcystis spp. 16S rRNA (MIC), and two toxin biosynthetic genes (mcyB and mcyD) and are given in Hotto et al (2005).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have focused on detection of the mcy genes using a PCR approach with species-specific primers based on differences within the mcy gene clusters (18,20,26,32,36,47) as well as universal primers targeting conserved sequences of the MC operon (14,17). The common mcy genes targeted are mcyA, -B, -C, -D, and -E, with many studies using a combination of the genes (15,26,27,33,44,48). Several studies have indicated that MC-producing Microcystis spp.…”
Section: Nostoc and Planktothrix Species The Generic Structure Of Amentioning
confidence: 99%
“…Extracts were clarified by centrifugation at 27,000 ϫ g followed by filtration through a 0.45-m nylon syringe filter and stored at Ϫ20°C. MC concentrations were determined using a PPIA, modified from Carmichael and An (7), run in 96-well plates (15). MC variants were identified from concentrated samples (10 to 20ϫ) by highperformance LC (Ace 5 C 18 column, 4.6 by 250 mm) with PDA and MS detectors using a gradient of 30 to 70% acetonitrile in water, both acidified to 0.1% (vol/vol) with trifluoroacetic acid.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation